Old galaxies at high redshift - Dalton, G (2001)
We review the observational data available on the class of galaxies known as Extremely Red Objects (EROs), and present new data on their apparent surface density, which now appears to be much higher than has previously been claimed. We discuss the division of these objects into two distinct groups: young galaxies with dramatic ongoing star formation and old galaxies with highly evolved stellar populations. Age-determination for the latter group using population synthesis models is complicated by an intrinsic degeneracy between the age and initial metallicity of the stellar populations.